Content Validity of Flipped Learning-Based Statistical Learning Evaluation Instruments at Tourism Colleges - Sugiharni, Gusti Ayu Dessy (LPPM Undiksha, 2023)
The problem that occurs is that there are still many researchers who have not paid attention to the content validity of the evaluation instruments used in evaluation activities. Seeing the important role of the evaluation instrument as a measuring tool, it is necessary to determine the content validity of the evaluation instrument. This study aims to show in detail the process of calculating the content validity of an evaluation instrument that is specifically used in evaluating the quality of statistical learning based on flipped learning at tourism tertiary institutions after the Covid-19 pandemic. This type of research is the development of instruments using a quantitative approach. The subjects of this study were several experts who were involved in testing the content validity of the evaluation instrument. The number of experts involved was 4 experts, including: 1 expert in mathematics education, 1 expert in tourism, 1 expert in informatics engineering education, and 1 expert in education evaluation. The tool used by experts to assess the evaluation instrument items is a questionnaire consisting of 26 questions. The formula used to analyze the results of the content validity test of the evaluation instrument is Aiken. The data analysis technique for the results of the content validity test was carried out by comparing the results of the average value of V from the calculation of the Aiken formula with the Gregory validity categorization. The results showed that 18 valid instruments and 8 invalid instruments. In addition, from the average V value of 0.668, it can be stated that the evaluation instrument specifically used in evaluating the quality of statistical learning based on flipped learning at tourism tertiary institutions after the Covid-19 pandemic is classified as high validity.